Pelatihan Manajemen Waktu pada Komunitas Mahasiswa Islam - Diana Anindita; M.Mawahib Ahyauddin; Siti Hikmah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
The time management training for the Islamic Student Community aimed to enhance understanding and skills in effective time management to reduce procrastination and increase productivity. The methods utilized included capacity-building-based psychoeducation, material delivery, and practical exercises using the Eisenhower matrix. The intervention was conducted in three stages: initial data collection, material presentation, and practical training. Seven community members participated in the program. Evaluation results showed an average pre-test score improvement from 40 to 95.7 in the post-test, indicating the intervention's success in fostering more disciplined and organized behavior. The program is recommended for continuous implementation to support the capacity development of individuals and the community.